1997
DOI: 10.1093/ee/26.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ambient and Leaf Litter Temperatures in Overwintering Habitats of Boll Weevil (Coleoptera: Curculionidae)

Abstract: Temperature data are unavailable for most boll weevil overwintering habitats. As a result, ambient data often are used to estimate overwintering survival and emergence. In this study, relationship of ambient and overwintering habitat temperatures was determined for 6 habitats in the Rolling Plains of Texas. The amplitude of the daily temperature cycle in the leaf litter of each habitat was dampened compared with that recorded for ambient. Average minimum daily leaf litter temperature was 3.19"C higher in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…2003;andlate, 2 April 2002 and19 Mar. 2003. c of DD would require intimate knowledge of overwintering habitat and insulation, and ambient air temperatures overestimate positive DD by 6.5Ð15.7% (Parajulee et al 1997). Stone et al (1990) reported that, over a 7-yr study, the variation in emergence patterns can be Ͼ30 d. Although Parajulee et al (2001) developed a model for boll weevil survivorship on the Rolling Plains, overwintering habitats, food sources (Chandler and Wright 1991), the timing of weevil entry into overwintering habitat (Sterling 1971, Wade and, the date at which to begin calculating DD (Parajulee et al 1996), and the relative incidence of diapause, among other conceivable parameters, would differ in subtropical and tropical conditions where boll weevils are active and reproducing year-round (Guerra et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…2003;andlate, 2 April 2002 and19 Mar. 2003. c of DD would require intimate knowledge of overwintering habitat and insulation, and ambient air temperatures overestimate positive DD by 6.5Ð15.7% (Parajulee et al 1997). Stone et al (1990) reported that, over a 7-yr study, the variation in emergence patterns can be Ͼ30 d. Although Parajulee et al (2001) developed a model for boll weevil survivorship on the Rolling Plains, overwintering habitats, food sources (Chandler and Wright 1991), the timing of weevil entry into overwintering habitat (Sterling 1971, Wade and, the date at which to begin calculating DD (Parajulee et al 1996), and the relative incidence of diapause, among other conceivable parameters, would differ in subtropical and tropical conditions where boll weevils are active and reproducing year-round (Guerra et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Positive degree-days (DD) (Ͼ0.0ЊC) were calculated using the daily minimum and maximum temperature method (Parajulee et al 1997). The threshold (0.0ЊC) for positive degree-days was estimated as the mean of the average daily minimum temperature between mid-February and early March, or just 2 wk immediately before the initiation of moth ßight to pheromone traps.…”
Section: Methodsmentioning
confidence: 99%
“…Among the years of study, 1980 was the coldest, with only 70 positive degree-days (DD) accumulated during the Þrst month of overwintering and 785 DD accumulated during the entire overwintering period of 185 d. In contrast, 336 and 1887 DD were accumulated during the Þrst month of overwintering and during the entire overwintering period of 188 d, respectively, in 1991. The total negative degree-days (NDD) also varied among years, ranging from 0 NDD in 1979, 1997, 1998, and 1999to 25 NDD in 1989. The amount of rainfall during each dig-up month ranged from 0 to 13 cm.…”
Section: Resultsmentioning
confidence: 99%
“…In the Texas Plains, boll weevils initiate diapause in early August (Sterling and Adkisson 1974), with spring/ summer emergence from overwintering habitats continuing to late July the following year Rummel 1985, Slosser andFuchs 1991). The proportion of diapausing weevils that successfully overwinter is dependent on boll weevil overwintering survival potential (Rummel et al 1999), timing of weevil entry into overwintering habitat (Sterling 1971, Wade and Rummel 1978, Rummel and Carroll 1983, Parajulee et al 1996, winter severity as reßected by low temperatures and rainfall (Pfrimmer and Merkl 1981, Price et al 1985, Stone et al 1990, and by the insulating capacity of the overwintering habitat (Slosser et al 1984, Slosser and Fuchs 1991, Carroll et al 1993, Parajulee et al 1997.…”
mentioning
confidence: 99%